Mixed Hyperglycemic Crisis in a Young Obese DiabeticTriggered by Hypertriglyceridemia-Induced Pancreatitis:A Case Report and Review of Pathophysiolo - Teuku Mirzal Safari; Agustia Sukri Ekadamayanti; Krishna W. Sucipto; Hendra Zufry (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2025)
Mixed diabetic ketoacidosis (DKA) and hyperglycemic hyperosmolar state (HHS), accompanied by hypertriglyceridemia-induced pancreatitis, represent a rare but life-threatening complication of type 2 diabetes mellitus (T2DM). This case report aimed to illustrate a young adult in whom these three critical conditions converged, highlighting the complexity of such presentations—a 28-year-old male presented with altered consciousness and Kussmaul respiration. The patient was diagnosed with T2DM two weeks earlier but had not yet initiated treatment. Physical examination revealed obesity (BMI: 31 kg/m²) and acanthosis nigricans on the neck and in the axillary regions. Laboratory results showed hyperglycemia (798 mg/dL), metabolic acidosis (pH: 7.08; anion gap: 24), ketonuria, hyperosmolarity (336 mOsm/kg), severe hypertriglyceridemia (965 mg/dL), and elevated lipase (892 U/L). A diagnosis of mixed DKA-HHS secondary to hypertriglyceridemic pancreatitis was established. Treatment included aggressive intravenous (IV) fluid resuscitation of 0.9% sodium chloride (6 L in the first 12 hours) and insulin infusion (0.1 units/kg/hour). During hospitalization, the patient developed acute kidney injury, necessitating continuous renal replacement therapy (CRRT). The patient gradually recovered and was discharged after 20 days. In obese T2DM patients, insulin resistance drives severe hyperglycemia typical of HHS. However, metabolic stress caused by acute pancreatitis induces relative insulin deficiency, triggering lipolysis, ketogenesis, and hypertriglyceridemia, leading to overlapping DKA. Severe hypertriglyceridemia exacerbates systemic inflammation, insulin resistance, and ketosis, creating a vicious cycle that worsens mixed DKA-HHS. This case report highlights the importance of recognizing that T2DM can occasionally present with atypical, life-threatening metabolic complications, necessitatingprompt diagnosis and multidisciplinary management.